The Role of Strategic Management in Improving the Quality of Islamic Education in the Digital Era - Anik Indra Mustika; Mira Santika; Nasib Samsuri Lubis; Muslim Liyadi; Muhammad Syaifuddin (Journal of Practice Learning and Educational Development, 2025)
Islamic education in the digital era faces great challenges in adapting technology to improve the quality of learning and institutional management. Strategic management plays a key role in developing relevant and effective policies to manage these changes. This article discusses the role of strategic management in improving the quality of Islamic education through the use of technology, the development of digital-based curriculum, and teacher capacity building. The suggested strategic steps include integrating technology into online learning, developing a curriculum that is responsive to technological developments, and training teachers to master educational technology. Despite challenges such as inequality of access to technology and resistance to change, the implementation of proper strategic management can create a generation of religious knowledge and technology. In this way, Islamic education can develop and remain relevant in the face of digital advancements.